Green Plant Pigment, Chlorophyllin, Ameliorates Non-alcoholic Fatty Liver Diseases (NAFLDs) Through Modulating Gut Microbiome in Mice - Yang, You; Jiang, Xile; Pandol, Stephen J.; Han, Yuan-Ping; Zheng, Xiaofeng (Frontiers in Physiology, 2021)
Nonalcoholic fatty liver diseases (NAFLD) along with metabolic syndrome and type-2 diabetes is increasingly prevalent worldwide. Without effective resolution, simple hepatic steatosis may prognose to non-alcoholic steatohepatitis (NASH), characterized as hepatocyte damage, chronic inflammation, necrosis, fatty degeneration, and cirrhosis. Gut microbiome is vital for metabolic homeostasis. Conversely, dysbiosis contributes to metabolic diseases including NAFLD. Specifically, diet composition is critical for enterotype of gut microbiota. We reasoned that green pigment richen in vegetable, chlorophyll, may modulate gut microbiome for metabolic homeostasis. In this study, C57BL/6 mice under high fat diet (HFD) was treated with sodium copper chlorophyllin (CHL), a water-soluble derivative of chlorophyll, in drinking water. After 28 weeks of HFD feeding, liver steatosis model was established accompanied with gut microbiota dysbiosis, intestinal impairment, endotoxemia, systemic inflammation, and insulin resistance. Administration of chlorophyllin effectively alleviated systemic and intestinal inflammation, and maintained tight junction in intestinal barrier. Chlorophyllin rebalanced gut microbiota in the mice subjected high fat feeding, and attenuated hepatic steatosis, insulin resistance, dyslipidemia, and reduced body weight. Fecal flora transplant from the CHL-treated mice ameliorated steatosis as well. Thus, dietary green pigment or administration of chlorophyllin can maintain gut eubiosis and intestinal integrity to attenuate systemic inflammation and relieve non-alcoholic steatohepatitis.